Konstruksi Sosial Masyarakat Terhadap Praktek Mengemis Di Quburan Bonoloyo Banjarsari Surakarta - Megarani, Sofi Nur; Rahman, Abdul; Yuhastina, Yuhastina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Beggars are important social problems and emergency to solve by society and government. Located in Surakarta, Bonoloyo cemetery is one of the public cemeteries used by beggars to make a daily living. The growing beggars at the tomb raises social economic perceptions supported by data were obtained with observations, interviews and documentation involving seven informants. Then data was analysed with Miles & Huberman’s technic including through four step: data collection, display, reduction, and conclusions. Finding indicated that people around the Bonoloyo Cemetery have long used public cemeteries as a place to make a living, they have stimulated their descendants. In the process of its development, there are aspect that build the social construction of beggars, including externalization, objectivation, and internalization. Thus making the practice of begging able to survive from generation to generation.